Vital subjects : race and biopolitics in Italy, 1860-1920 - Welch, Rhiannon Noel (2016)
Vital subjects: race and biopolitics in Italy is an interdisciplinary study of how racial and colonial discourses shaped the “making” of Italians as modern political subjects in the years between its administrative unification (1861-1870) and the end of the First World War (1919)